Audit Rates and Compliance: A Field Experiment in Long-term Care - Maarten Lindeboom; Bas van der Klaauw; Sandra Vriend (Tinbergen Institute, 2014)
We provide evidence from a large-scale field experiment on the causal effects of audit rules on compliance in a market for long-term care. In this setting care should be provided quickly and, therefore, the gatekeeper introduced ex-post auditing. Our results do not show significant effects of variations in random audit rates and switching to a conditional audit regime on the quantity and quality of applications for care. We also do not find evidence for heterogeneous effects across care providers differing in size or hospital status. Our preferred explanation for the lack of audit effects is the absence of direct sanctions for noncompliance. The observed divergence of audit rates in the conditional audit regime is the consequence of sorting and thus identifies the quality of application behavior of providers.
Keywords: C93; H51; I18; 330; auditing; field experiment; compliance; feedback; long-term care